Domborművek. - (Irmédi-Molnár László) (Fond 165 Irmédi-Molnár László)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László művei és anyaggyűjtései kül. témákhoz > A Térképalkotás c. műből kimaradt fejezetek